Cytoskeletal Remodeling in Cancer - Jaya Aseervatham (Biology, 2020)
Successful metastasis depends on cell invasion, migration, host immune escape, extravasation, and angiogenesis. The process of cell invasion and migration relies on the dynamic changes taking place in the cytoskeletal components; actin, tubulin and intermediate filaments. This is possible due to the plasticity of the cytoskeleton and coordinated action of all the three, is crucial for the process of metastasis from the primary site. Changes in cellular architecture by internal clues will affect the cell functions leading to the formation of different protrusions like lamellipodia, filopodia, and invadopodia that help in cell migration eventually leading to metastasis, which is life threatening than the formation of neoplasms. Understanding the signaling mechanisms involved, will give a better insight of the changes during metastasis, which will eventually help targeting proteins for treatment resulting in reduced mortality and longer survival.